2018
DOI: 10.31055/1851.2372.v53.n2.20574
|View full text |Cite
|
Sign up to set email alerts
|

Xylariales): Physiological characterization and structural features of its association with wheat.

Abstract: Summary: Plant roots can be colonized by asymptomatic fungal strains belonging to several taxa, among them, the group defined as Dark Septate Endophytes (DSE). Microdochium bolleyi commonly colonizes wheat roots and other crops. It is considered a weak pathogen or even a non-pathogenic fungal species, which has also been considered as a potential biocontrol agent against aggressive soil-borne pathogens in cereal crops. We isolated a strain of M. bolleyi from wheat roots sampled in a crop field in Argentina, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Infestation with this pathogen allows other fungi to colonize host tissues, include highly virulent pathogens represented by F. culmorum , or other weaker or non-pathogenic species of fungi such as Microdochium bolleyi [ 41 ]. M. bolleyi can be considered as a potential biocontrol agent against aggressive soil-borne pathogens in cereal crops [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infestation with this pathogen allows other fungi to colonize host tissues, include highly virulent pathogens represented by F. culmorum , or other weaker or non-pathogenic species of fungi such as Microdochium bolleyi [ 41 ]. M. bolleyi can be considered as a potential biocontrol agent against aggressive soil-borne pathogens in cereal crops [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the enzymes that are considered as major PCWDEs (cellulases, xylanases, pectinases, proteases, and lignin peroxidases) have not been analyzed for the members of Microdochium genus. The only extracellular enzymatic activities described for Microdochium species are amylase and invertase (non-PCWDEs) and glucosidase and galactosidase ("minor" PCWDEs) [44,74,141]. In our study, we showed that, in addition to extracellular amylase and invertase, Microdochium strains produce extracellular cellulase (endoglucanase), protease, lignin peroxidase, xylanase, arabinofuranosidase, and pectate lyase.…”
Section: Microdochium Nivale Strains Associated With Rye Snow Mold: M...mentioning
confidence: 52%
“…Second, it is possible that the deferential pathogenicity of M. nivale and M. bolleyi is determined not by the set of virulence factors but by the regulatory networks coordinating their production. Third, although M. bolleyi has been described as a non-phytopathogenic root endophyte (Rothen et al 2018 ), it cannot be ruled out that, under specific conditions, it is also able to cause disease and thus manifest phytopathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Orthologous groups of proteins were identified using OrthoFinder with default settings. The orthologs were searched in the reference proteomes of M. nivale and three other Ascomycota species, M. bolleyi , Sclerotinia borealis , and Fusarium graminearum with contrasting lifestyles: M. bolleyi is a non-psychrotolernat and non-phytopathogenic species (Rothen et al 2018 ), S. borealis is a snow mold-causing psychrophilic species (Hoshino et al 2010 ), and F. graminearum is a mesophilic head blight causal agent (Goswami and Kistler 2004 ).…”
Section: Methodsmentioning
confidence: 99%